Flexible Generation of E-Learning Exams in R: Moodle Quizzes, OLAT Assessments, and Beyond - Achim Zeileis; Nikolaus Umlauf; Friedrich Leisch (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2012)
The capabilities of the package exams for automatic generation of (statistical) exams in R are extended by adding support for learning management systems: As in earlier versions of the package exam generation is still based on separate Sweave files for each exercise - but rather than just producing different types of PDF output files, the package can now render the same exercises into a wide variety of output formats. These include HTML (with various options for displaying mathematical content) and XML specifications for online exams in learning management systems such as Moodle or OLAT. This flexibility is accomplished by a new modular and extensible design of the package that allows for reading all weaved exercises into R and managing associated supplementary files (such as graphics or data files). The manuscript discusses the readily available user interfaces, the design of the underlying infrastructure, and how new functionality can be built on top of the existing tools.
Keywords: A2; C88; 330; exams; e-learning; multiple choice; arithmetic problems; Sweave; R; LaTeX; HTML; XML; IMS QTI; Moodle; OLAT